2019
DOI: 10.1080/21691401.2019.1606007
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA UCA1 exerts growth modulation by miR-15a in human thyroid cancer TPC-1 cells

Abstract: Thyroid cancer is widely diagnosed as malignancy in endocrine system. This study attempted to validate UCA1 possessed modulatory function on cell proliferation and epithelial mesenchymal transition (EMT) in human thyroid cancer cell line TPC-1. Ectopic expression of UCA1 was induced in TPC-1 cells by transfection. CCK-8 assays were employed to value cell viability. Cell apoptosis analysis was conducted through flow cytometry. We found that overexpressed UCA1 strongly promoted cell proliferation. However, the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Knockdown of UCA1 decreased DLL4 expression of renal cancer cells in vivo (g). Data were shown as mean ± standard deviation (SD) of those biological replicates or samples (*P < 0.05, **P < 0.01) [28][29][30], and our study is also a good example on the relation furthermore. LncRNAs function as miRNAs sponges or decoys that titrate the concentration of miR-NAs and therefore prevent miRNAs binding specific mRNAs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Knockdown of UCA1 decreased DLL4 expression of renal cancer cells in vivo (g). Data were shown as mean ± standard deviation (SD) of those biological replicates or samples (*P < 0.05, **P < 0.01) [28][29][30], and our study is also a good example on the relation furthermore. LncRNAs function as miRNAs sponges or decoys that titrate the concentration of miR-NAs and therefore prevent miRNAs binding specific mRNAs.…”
Section: Discussionmentioning
confidence: 87%
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA UCA1 was found to be aberrantly expressed in various cancer tissues [6,7,47] and multiple studies indicated that UCA1 worked as an oncogene in cancers. For instance, UCA1 deletion suppressed cell invasion and colony survival fraction, and induced cell cycle arrest by inhibiting EMT progression in colorectal cancer [48].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (LncRNAs), as crucial modulators, participate in the initiation and development of many diseases, including cancers [ 3 5 ]. Urothelial cancer associated-1 (UCA1) was identified as an oncogene in various cancers [ 6 8 ]. For example, overexpression of UCA1 promoted the progression of breast cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%